Bioatividade da semente de abacate (Persea americana Mill) sobre Atta sexdens Forel, 1908 (Hymenoptera: Formicidae) - Zanini, Juliana Keppe (2023)
Leaf-cutting ants are insects of great agricultural importance due to their harmful attack on different production systems, resulting in large economic and production losses. Currently, the use of chemicals to control these insects is the most used method, however, this has been associated with various environmental and human damages. Faced with the need for new alternatives with less environmental impact, the objective of this work was to evaluate the potential of avocado seed oil to control leaf-cutting ants. Oil extraction was carried out at the Contaminant Waste Laboratory – LRC (Embrapa Meio Ambiente), using soxhlet-type extractor devices, using hexane as a solvent. For the topical tests, 180 Atta sexdens workers were collected and used five different volumes of oil and a control treatment: control 0.5 μL (distilled water), V1 - 0.25; V2 - 0.5; V3 - 0.75; V4 - 1.0 and V5 - 2.0μL. The oil was applied topically on the workers' pronotum, which were then individualized and kept in BOD at 24 ± 2°C. The evaluations occurred every 24 hours, for eight days. In the evaluation of topical toxicity, for both tests, mortality rates were higher in the first days after application of the oil, but the results referring to the second topical test were more promising concerning the first test. This factor may be due to the higher proportion of linoleic acid present in the oil from the second extraction, which was used in the second topical test. The accumulated mortality of the control treatments was high in both tests and for this reason, further studies are needed to explain such results. The different volumes evaluated did not present significant differences among themselves, only for the control treatment. From the chemical analysis of the oil, performed by the GC-MS and GC-FID method, several non-saponifiable and saponifiable compounds were identified, among them linoleic, palmitic, oleic, alpha-linoleic and myristic fatty acids. Linoleic acid showed a higher proportion in both oil samples, being the compound most commonly associated with the observed insecticidal activities. Regarding the subcolonies, 30 pellets were offered per treatment: control pellets (without oil) and pellets containing 0.5 μL of avocado seed oil, totaling eight repetitions and 120 pellets each. The evaluation of the number of dead workers and the loading of baits occurred every 24 hours, for six days. The number of pellets containing the oil carried by the workers was low, however, it was possible to observe a higher mortality in the control treatment.